Objectively measured sedentary behaviour and health and development in children and adolescents: systematic review and meta‐analysis. (24th February 2016) - Cliff, D. P.; Hesketh, K. D.; Vella, S. A.; Hinkley, T.; Tsiros, M. D.; Ridgers, N. D.; Carver, A.; Veitch, J.; Parrish, A.‐M.; Hardy, L. L.; Plotnikoff, R. C.; Okely, A. D.; et al.
Summary: Sedentary behaviour has emerged as a unique determinant of health in adults. Studies in children and adolescents have been less consistent. We reviewed the evidence to determine if the total volume and patterns (i.e. breaks and bouts) of objectively measured sedentary behaviour were associated with adverse health outcomes in young people, independent of moderate‐intensity to vigorous‐intensity physical activity. Four electronic databases (EMBASE MEDLINE, Ovid EMBASE, PubMed and Scopus) were searched (up to 12 November 2015) to retrieve studies among 2‐ to 18‐year‐olds, which used cross‐sectional, longitudinal or experimental designs, and examined associations with health outcomes (adiposity, cardio‐metabolic, fitness, respiratory, bone/musculoskeletal, psychosocial, cognition/academic achievement, gross motor development and other outcomes). Based on 88 eligible observational studies, level of evidence grading and quantitative meta‐analyses indicated that there is limited available evidence that the total volume or patterns of sedentary behaviour are associated with health in children and adolescents when accounting for moderate‐intensity to vigorous‐intensity physical activity or focusing on studies with low risk of bias. Quality evidence from studies with robust designs and methods, objective measures of sitting, examining associations for various health outcomes, is needed to better understand if the overall volume or patterns of sedentary behaviour are independent determinants of health in children and adolescents.